Effect of Process Parameters on Weld Joint Quality During Submerged ARC Welding of HSLA Steel - Garg, Manish (My University, 2012)
The aim of the present work was to study the effect of various process parameters i.e. current, voltage, travel speed, electrode diameter, flux composition, pre heating of workpiece, electrode stick-out and edge including angle on changes in tensile strength, toughness, microhardness and chemical composition of the weld bead geometry of HSLA Steel and to optimize the process so that minimal changes occur in the material properties after completion of a submerged arc welding (SAW) process following suitable Taguchi experimental design. Tensile strength of the welded specimens were studied and found that Electrode Diameter, welding current and travel speed were the most significant factors leading to changes in tensile strength. The tensile strength tended to increase significantly with the increase in electrode diameter from 3.2-4 mm. whereas higher tensile strength was observed when welding current 450 Ampere and travel speed 15 m/hr was used. Toughness at room temperature of the welded specimen were studied and found that Electrode diameter, electrode stick-out, current, preheat temperature, voltage were the most significant factors and higher toughness at room temperature was observed when electrode diameter should be 3.2 mm, electrode stick-out should be 28 mm, welding current should be 350 Ampere, preheat temperature should be 150 oC and welding voltage should be 30 Volts and flux should be of type 3 i.e. GEEFLUX 541 (Basic) was used. Toughness at -40 oC of the welded specimens were studied and found that type of flux, welding current and electrode stick-out were the most significant factors and higher toughness was observed when welding current 450 Ampere, flux type 3 (GEEFLUX 541-Basic) and electrode stick-out should be 28 mm was used. Edge including angle and welding current were found to be the most significant factors leading to changes in microhardness. The microhardness tended to increase significantly with the increase of welding current from 350 to 450 Ampere and as the edge including angle increases from 60 to 90 degree, microhardness will decrease. Chemical composition of welding specimen was also studied and found that percentage change in phosphorous was increasing in weld region but carbon, sulphur, nickel and chromium contents were decreasing whereas for silicon, manganese and copper shows the mixed trend. So, it concludes that some compounds of flux goes into the weld region.
M.E. (CAD/CAM and Robotics)
Keywords: Submerged Arc welding; HSLA steel; tensile strength; toughness; microhardness; process parameters